Stimulatory Effect of Indole – 3 – Butyric Acid and Rooting Media on Adventitious Rooting in Epipremnum Aureum ‘Marble Queen’ Stem Cuttings - Attanayake R.M.T.D; Dasanayaka Y.M.H.M.H; Dilshan H.K.L; Hettiarachchi W.A.B.H; Sandarenu K.M.S.D; Gamage S.N.W; Wickramasinghe P.A.S.C; Dayarathna C.R; Kumarihami H.M.P.C (Indonesian Journal of Applied Research (IJAR), 2023)
Epipremnum aureum 'Marble Queen' has high demand in the floriculture industry and is propagated commercially using single nodal stem cuttings. In the floriculture industry, they are exported as rooted and unrooted cuttings. Two experiments were conducted to determine the rooting performance of 'Marble Queen' cuttings for both rooted and unrooted export purposes. Experiment one tested the rooting performances of unrooted cuttings after an export simulation (48-hour cold storage at 21°C). In experiment two, the effect of rooting media and IBA was evaluated to produce rooted cuttings. Two different rooting media (coir dust and oasis) and four different concentrations of IBA (0 mg·L-1, 250 mg·L-1, 500 mg·L-1, and 1000 mg·L-1) were tested. Rooting media showed the most significant effects on the rooting of 'Marble Queen' cuttings. Coir dust medium reported the highest number of roots per cutting, root-to-shoot ratio, and average root diameter. Minimum days to bud and root initiation and a higher number of leaf buds were observed in the oasis medium. Early rooting and a higher number of roots were observed with the application of 500 mg·L-1 IBA. The use of an appropriate rooting medium and optimum concentration of IBA would help in the rapid propagation of 'Marble Queen' cuttings. Applying 500 mg·L-1 IBA in the oasis medium was more efficient in early rooting and shoot growth of 'Marble Queen' cuttings. Coir dust medium, along with 500 mg·L-1 IBA, was most suitable for the efficient growth and development of 'Marble Queen' cuttings.